2020
DOI: 10.1038/s41421-020-0150-6
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of REF6 and its complex with DNA reveal diverse recognition mechanisms

Abstract: Relative of Early Flowing 6 (REF6) is a DNA-sequence-specific H3K27me3/2 demethylase that contains four zinc finger (ZnF) domains and targets several thousand genes in Arabidopsis thaliana. The ZnF domains are essential for binding target genes, but the structural basis remains unclear. Here, we determined crystal structures of the ZnF domains and REF6-DNA complex, revealing a unique REF6-family-specific half-cross-braced ZnF (RCZ) domain and two C2H2-type ZnFs. DNA-binding induces a profound conformational ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…Consistent with this, REF6 functions as a DNA sequence-specific H3K27me3 demethylase. Genomewide REF6 binding studies and crystal structure analysis revealed that the ZnF domains of REF6 recognize the CTCTGYTY DNA motif for H3K27me3 removal (Figures 1B, 2A) (Cui et al, 2016;Li et al, 2016;Tian et al, 2020). The ZnF domains of REF6 complex with NAC004 double-stranded (ds) DNA by forming a half-cross-braced structure (Figure 1B).…”
Section: Protein Structure and Chromatin-targeting Mechanisms Of H3k27 Demethylasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with this, REF6 functions as a DNA sequence-specific H3K27me3 demethylase. Genomewide REF6 binding studies and crystal structure analysis revealed that the ZnF domains of REF6 recognize the CTCTGYTY DNA motif for H3K27me3 removal (Figures 1B, 2A) (Cui et al, 2016;Li et al, 2016;Tian et al, 2020). The ZnF domains of REF6 complex with NAC004 double-stranded (ds) DNA by forming a half-cross-braced structure (Figure 1B).…”
Section: Protein Structure and Chromatin-targeting Mechanisms Of H3k27 Demethylasesmentioning
confidence: 99%
“…Interactions at the interface between REF6 and dsDNA, such as hydrogen bonds, electrostatic interactions, and hydrophobic interactions, strengthen their binding. dsDNA binding induces profound conformation changes (Tian et al, 2020). Conformational plasticity of DNA allows REF6 to recognize diverse target genes.…”
Section: Protein Structure and Chromatin-targeting Mechanisms Of H3k27 Demethylasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA motif discovery analyses defined that REF6 binds to a specific CTCTGYTY motif, where Y represents T or C ( Cui et al., 2016 ; Li et al., 2016 , 2018a ). This DNA-protein interaction has been proposed to define a novel half-cross braced ZnFn-type domain ( Tian et al., 2020 ). Interestingly, REF6 binding to DNA is inhibited by DNA methylation which explains why REF6 is depleted from heterochromatin regions in the genome ( Qiu et al., 2019 ; Tian et al., 2020 ).…”
Section: Ref6mentioning
confidence: 99%
“…This DNA-protein interaction has been proposed to define a novel half-cross braced ZnFn-type domain ( Tian et al., 2020 ). Interestingly, REF6 binding to DNA is inhibited by DNA methylation which explains why REF6 is depleted from heterochromatin regions in the genome ( Qiu et al., 2019 ; Tian et al., 2020 ).…”
Section: Ref6mentioning
confidence: 99%